A Comparative Corpus-based Analysis of Boosters in NESs and NNESs' Academic Articles - Oz, Gulsah (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The purpose of the current study was to examine the frequently used boosters in academic articles written by Native (NESs) and Non-native (NNESs) Speakers of English (Turkish researchers) in the field of English Language Teaching. Investigating whether differences exist in the use of these markers between NESs and NNESs’ academic articles was another aim of the study. Within this purpose, data was collected from one hundred academic articles (NESs= 50, NNESs= 50 articles) published between 2016 and 2021 in two different international journals indexed in ERIC by using the keyword ‘English Language Teacher Education’, and the data were analysed using AntConc concordance tool. Log-likelihood statistics were run to find out whether any significant difference exists between NESs and NNESs’ use of boosters in terms of frequency. The analysis revealed that statistically significant underuse of boosters by NESs writers in terms of their use of types of boosters was found.